The effectiveness of critical time intervention for abused women leaving women’s shelters: a randomized controlled trial - Beijersbergen, Marielle D. (2018)
Objectives: To examine the effectiveness of critical time intervention (CTI)—an evidence-based intervention—for abused women transitioning from women’s shelters to community living. Methods A randomized controlled trial was conducted in nine women’s shelters across the Netherlands. 136 women were assigned to CTI (n = 70) or care-as-usual (n = 66). Data were analyzed using intention-to-treat three-level mixed-effects models. Results: Women in the CTI group had signiﬁcant fewer symptoms of post-traumatic stress (secondary outcome) (adjusted mean difference - 7.27, 95% CI - 14.31 to - 0.22) and a signiﬁcant fourfold reduction in unmet care needs (intermediate outcome) (95% CI 0.06–0.94) compared to women in the care-as-usual group. No differences were found for quality of life (primary outcome), re-abuse, symptoms of depression, psychological distress, self-esteem (secondary outcomes), family support, and social support (intermediate outcomes). Conclusions: This study shows that CTI is effective in a population of abused women in terms of a reduction of posttraumatic stress symptoms and unmet care needs. Because follow-up ended after the prescribed intervention period, further research is needed to determine the full long-term effects of CTI in this population